Livestock systems research in Nigeria's subhumid zone - Kaufmann, Ralph R. von; Chater, S.; Blench, Roger (International Livestock Centre for Africa, 1986)
Compilation of proceedings of the 2nd ILCA/NAPRI symposium on livestock production in subhumid Nigeria discussing the ecology, vegetation & land use & development potential of the zone; traditional cattle & small ruminant production practices; research updates in livestock systems research, animal nutrition & feed production; extension & adoption of innovations; and future research.